Case Report: Intussusception in an Infant with Respiratory Syncytial Virus (RSV) Infection and Post-Operative Wound Dehiscence - Makalo, Lamin; Ruiz Perez, Orlianys; Martin, Benjamin; S Jallow, Cherno; Lamin Jobarteh, Momodou; Baldeh, Alagie; Malik Fye, Abdul; Jitteh, Fatoumatta; Bah, Isatou (Journal of Community Medicine and Health Solutions, 2025)
Intussusception is a leading cause of intestinal obstruction in young children, typically presenting with colicky abdominal pain and altered stool characteristics, before progressing to abdominal distension and bilious vomiting. This case report describes an 8-month-old male who presented with gastrointestinal symptoms, respiratory distress, and signs of intestinal obstruction. The patient was diagnosed with intussusception and found to be positive for Respiratory Syncytial Virus (RSV). After an attempted ultrasound-guided hydrostatic fluid enema, he underwent laparotomy to resolve the intussusception but developed post-operative complications, including delayed wound healing and wound dehiscence. The interplay of viral infections like RSV, and treatments such as steroids in pediatric surgical cases warrants further attention, especially concerning postoperative outcomes.